The Impact of Instructional Software in Developing Reading, Writing and Self-learning Skills in Reading and Writing Curriculum for the Students of the University of Jordan - Ayesha Khalfan Almuhairi (University of Science and Technology, Yemen, 2019)
This study aimed to investigate the impact of Instructional Software on the development of reading and writing and self-learning skills in the students of the University of Jordan. To achieve the study objecitves,  a questionnaire was developed to measure self-learning skills. After checking its validity and reliability, the questionniare was distributed to a sample of (60) students from the Jordan University in the second semester 2017/2018, who were divided into two groups: an experimental group (30) and a control group of (30) students. The experimental was taught using Instructional Software, whereas the control group was taught in the usual method. The results showed that there were statistically significant differences at the level of (α = 0.05) in the students' reading and writing skills in favor of the teaching method using the Instructional Software. There were also statistically significant differences at the level of significance (α = 0.05) in the four dimensions of self-learning scale: organizational skills, control and guidance, the use of learning resources and self-assessment, as well as in the scale as a whole. These differences were attributed to the teaching method in favor of the experimental group. The study recommended the use of Instructional Software to students of reading and writing on various subjects at the University of Jordan in order to benefit from the positive impact of the use of Instructional Software in the development of self-learning skills among the students of the Jordan University. It was also recommended to  study the effect of using Instructional Software on a variety of courses and for different levels of study. Keywords: Instructional software, Reading and writing skills, Self learning skills.